Interactions among spherical poly(acrylic acid) brushes: Observation by rheology and small angle X‐ray scattering. Issue 3 (28th September 2015) - Wang, Weihua; Chu, Fangfang; Li, Li; Han, Haoya; Tian, Yuchuan; Wang, Yunwei; Yuan, Zhenyu; Zhou, Zhiming; Guo, Xuhong
ABSTRACT: Interactions among annealed spherical polyelectrolyte brushes (SPB) in concentrated aqueous dispersion under the effect of concentration, pH, and salt concentration are investigated by means of rheology, and small angle X‐ray scattering (SAXS). SPB consist of a solid polystyrene (PS) core and linear poly(acrylic acid) (PAA) chains densely grafted onto the core by one end. Rheological investigation demonstrates that the viscosity, the storage modulus G ′ and the loss modulus G ″ of SPB dispersion increase significantly upon increasing the SPB concentration and pH value which reflects the enhanced interactions among SPB. At high pH, a further increase in pH from 8 to 13 has almost no impact on the rheological properties and SAXS curves, while a "Uniform Shell Model" can fit the SAXS data very well probably due to the uniform filling of polyelectrolyte chains among SPB. When increasing the salt concentration from 10 −5 to 10 −3  M, the so‐called "polyelectrolyte peak" appears at middle to high q range in SAXS curves which means the overlapped polyelectrolyte chains are associated under the bridging effect of counterions, which disappears at higher salt concentration due to the screening effect of further added salts. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 405–413 Abstract : Interactions among annealed spherical polyelectrolyte brushes (SPBs) in a concentrated aqueous dispersion under the effect of concentration, pH, and salt concentration are investigated systematically by means of rheology and small angle X‐ray scattering (SAXS). The results provide new insight into the interactions among SPBs at high concentrations, which can build up a solid foundation for the applications of SPBs.